Kajian Kriminologis Kekerasan Seksual Terhadap Anak - Syaranamual, Giovanny Franfol; Pasalbessy, John Dirk; Salamor, Yonna Beatrix (Faculty of Law, Universitas Pattimura, 2022)
Introductioan: The number of sexual violence against children every year is always high and even very disturbing and disturbing social and personal peace, therefore efforts to handle and overcome sexual violence must be handled carefully and firmly in accordance with applicable regulations.Purposes of the Research: The purpose of this study is to analyze and examine what criminogenic factors are the reasons someone commits a crime of sexual violence against children and discuss what steps or approaches are used to deal with sexual violence against children that occurs.Methods of the Research: the method used in this paper is an empirical juridical research method. The legal materials used are primary, secondary and tertiary legal materials.Results of the Research: The results of this study indicate that the criminogenic factor or reason for the perpetrators of sexual violence against children to take their actions is, because of an indication of supporting factors such as internal factors or factors from within the perpetrator and external factors or factors from outside the perpetrator. it can be explained that the handling efforts taken can be in the form of a penal approach or a legal approach and a non-penal approach or an illegal approach.